Cambodia Rice Sector Review : A More Detailed Road Map for Cambodian Rice Exports - World Bank (Washington, DC, 2015)
Cambodias rice exports are on a steep upward trajectory, benefiting from import duty preferences and new investments in rice mills and polishing factories. Cambodia’s major export competitors are Thailand and Vietnam. Thailand is a main competitor for fragrant rice, exporting itself ca 2.65 million tons of aromatic rice (including brokens) in 2010/2011. Vietnam is the principal competitor for the nonaromatic white rice markets such as the Philippines and Indonesia. Pakistan and Burma are competing with Cambodia for low-grade white rice markets mainly in Africa. The government needs to intensify its export facilitation efforts to increase its rice exports. Cambodia has reduced its milling costs but more needs to be done to improve competitiveness of its rice export. The capacity of Cambodia’s logistics system from mills to ports is inadequate to accommodate large-scale volumes. All of Cambodia’s rice exports are shipped in containers from Phnom Penh and Sihanoukville ports. Unless the government obtains a transit access to Saigon Port via the Mekong River for un-containerized milled rice, it is unlikely that Cambodia will export even 500,000 tons by 2015.